2003
DOI: 10.1038/emm.2003.16
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutations in sporadic deletional Duchenne muscular dystrophy (DMD) cases

Abstract: Dinucleotide repeat polymorphism based genetic analysis is a powerful approach to gain insight into rare genetic events like germline mosaicism and de novo mutations. The loss of heterozygosity of polym orphic dinucleotide loci at "deletional hotspot" of dystrophin gene can provide direct evidence of carrier status in female relatives of affected DMD patients with overlapped exonic deletions. We have used 4 STR loci of the central deletional hotspot of the dystrophin gene for genetic analysis in sporadic unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The carrier rate of deletion mutations was 60%, while that of the other classes of mutations ranged from 75 to 86% (Table 1 ). Our data was also consistent with Haldane’s theoretical model of de novo mutations in X-linked diseases, as well as research in this field [ 26 , 27 ], even though several smaller number studies showed that the carrier rate is much lower than the expected theoretical value [ 28 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…The carrier rate of deletion mutations was 60%, while that of the other classes of mutations ranged from 75 to 86% (Table 1 ). Our data was also consistent with Haldane’s theoretical model of de novo mutations in X-linked diseases, as well as research in this field [ 26 , 27 ], even though several smaller number studies showed that the carrier rate is much lower than the expected theoretical value [ 28 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…Families with DMD history showed anxiety and depression and strongly requested prenatal diagnosis. It has been known that 1/3 sporadic mutations of DMD gene occurs in male patients . Germinal mosaicism cases were detected in some DMD families .…”
Section: Discussionmentioning
confidence: 99%
“…We did not find a single TCF8 mutation shared by multiple families that might indicate a hotspot for mutation, and amplification of a simple-sequence repeat is not involved. One alternative basis for a high de novo mutation frequency would be reduced reproductive fitness of the mutant allele(s), but PPCD does not cause the kind of death or disability before reproductive age that is seen in some other disorders with many reports of germline mosaicism and de novo mutation such as DMD (Bullock et al 1996;Mukherjee et al 2003;Ferreiro et al 2004). It is interesting to note that, in the one family in which the mutation has been transmitted to progeny across four generations, the deletion is the most C-terminal of the mutations, which would leave most of the functional domains intact if the gene product is, indeed, produced ( fig.…”
Section: De Novo Mutationsmentioning
confidence: 99%